Trial Design Challenges and Approaches for Precision Oncology in Rare Tumors: Experiences of the Children’s Oncology Group - Renfro, Lindsay A. (JCO Precis Oncol, 2019)
In the United States, cancer remains the leading cause of disease-related death in children. Although survival from any pediatric cancer has improved dramatically during past decades, a number of cancers continue to yield dismal prognoses, which has motivated the continued study of novel therapeutic strategies. Furthermore, even patients cured of pediatric cancer often experience severe adverse effects of treatment and other long-term health implications, such as cardiotoxicity or loss of fertility. For these patients, improved risk stratification to identify those who could safely receive alternate or less-intensive therapy without affecting prognosis is a key objective. Fortunately, pediatric cancers are rare overall, but even among patients with the same narrow cancer type, there is often broad heterogeneity in terms of prognosis, molecular features or pathology, current treatment strategies, and scientific objectives. As a result, the design of clinical trials in the pediatric cancer setting is challenged by a number of practical issues that must be addressed to ensure trial feasibility for this vulnerable group of patients. In this review, we discuss some of the unique trial design considerations often encountered in any rare tumor setting through the lens of our experiences as faculty statisticians for the Children’s Oncology Group, the largest organization in the world dedicated exclusively to pediatric cancer research and clinical trials. These topics include risk stratification within individual trials, relaxation of trial operating characteristics and parameters, use of historical controls, and address of noninferiority-type objectives in small cohorts. We review each in terms of practical motivation, present challenges, and potential solutions described in the literature and implemented in selected example trials from the Children’s Oncology Group.